Non-redundant Functions of IL-6 Produced by Macrophages and Dendritic Cells in Allergic Airway Inflammation - Gubernatorova, Ekaterina O.; Gorshkova, Ekaterina A.; Namakanova, Olga A.; Zvartsev, Ruslan V.; Hidalgo, Juan; Drutskaya, Marina S.; Tumanov, Alexei V.; Nedospasov, Sergei A. (Frontiers in Immunology, 2018)
Asthma is a common inflammatory disease of the airway caused by a combination of genetic and environmental factors and characterized by airflow obstruction, wheezing, eosinophilia and neutrophilia of lungs and sputum. Similar to other proinflammatory cytokines, IL-6 is elevated in asthma and plays an active role in this disease. However, the exact molecular mechanism of IL-6 involvement in the pathogenesis of asthma remains largely unknown and the major cellular source of pathogenic IL-6 has not been defined. In the present study, we used conditional gene targeting to demonstrate that macrophages and dendritic cells are the critical sources of pathogenic IL-6 in acute HDM-induced asthma in mice. Complete genetic inactivation of IL-6 ameliorated the disease with significant decrease in eosinophilia in the lungs. Specific ablation of IL-6 in macrophages reduced key indicators of type 2 allergic inflammation, including eosinophil and Th2 cell accumulation in the lungs, production of IgE and expression of asthma-associated inflammatory mediators. In contrast, mice with deficiency of IL-6 in dendritic cells demonstrated attenuated neutrophilic, but regular eosinophilic response in HDM-induced asthma. Taken together, our results indicate that IL-6 plays a pathogenic role in the HDM-induced asthma model and that lung macrophages and dendritic cells are the predominant sources of pathogenic IL-6 but contribute differently to the disease.